MCA Microsoft 365 Certified Associate Modern Desktop Administrator Complete Study Guide Exam MD-100 and Exam MD-101 - Panek, William, 1970- (John Wiley & Sons, Incorporated, 2023)
Complete, UPDATED study guide for MCA Modern Desktop Administrator certification exams, MD-100 and MD-101. Covers new Windows 11, services, technologies, and more! MCA Microsoft 365 Certified Associate Modern Desktop Administrator Complete Study Guide, Second Edition, is your all-in-one guide to preparing for the exams that will earn you the MCA Modern Desktop Administrator certification! In this book, well-known Windows guru and five-time Microsoft MVP, William Panek, guides you through the latest versions of the Windows Client exam (MD-100) and the Managing Modern Desktops exam (MD-101). This one-stop resource covers 100% of the objectives for both exams, providing real world scenarios, hands-on exercises, and challenging review questions. You'll also dive deeper into some of the more complex topics and technologies, including deploying, maintaining, and upgrading Windows; managing devices and data; configuring storage and connectivity; managing apps and data; and more. Learn everything you need to know to pass the MD-100 and MD-101 exams Earn your MCA Modern Desktop Administrator certification to launch or advance your career Access exercises, review questions, flashcards, and practice exams, in the book and online Master all of the test objectives for the latest exam versions--updated for Windows 11 With this study guide, you also get access to Sybex's superior online learning environment, including an assessment test, hundreds of practice exams, flashcards, searchable glossary, and videos for many of the chapter exercises. This is the perfect test prep resource for admins preparing for certification and anyone looking to upgrade their existing skills to Microsoft's latest desktop client.